Analysis of the administration of large taxpayers, that is, those with a state share, "based on the experience of foreign countries" - Erkabaev Nuriddin Akhmadjonovich (Genius Journals, 2025)
This article discusses the role and importance of the interregional tax inspection in improving large-scale reforms aimed at creating favorable conditions for conducting business activities in the tax sphere in the country and further strengthening the confidence of business circles. At the same time, some important reforms being implemented in the tax system of Uzbekistan with a state share are studied, foreign experience is studied, scientific and practical conclusions and proposals are developed on its application in our country.
Keywords: tax policy; tax revenues; threat analysis